The Great Vietnamese Famine of 1944-45 Revisited - Geoffrey Gunn (Japan Focus)
The deaths stemming from the great famine of 1944-45, which reached its zenith in March-April 1945 in Japanese-occupied northern Vietnam, eclipsed in scale all human tragedies of the modern period in that country up until that time. The demographics vary from French estimates of 600,000-700,000 dead, to official Vietnamese numbers of 1,000,000 to 2,000,000 victims.1 Food security is an age-old problem, and dearth, famine, and disease have long been a scourge of mankind across the broad Eurasian landmass and beyond. While more recent understandings2 recognize that famines are mostly man-made, it is also true that in ecologically vulnerable zones, alongside natural disasters, war and conflict often tilts the balance between sustainability and human disaster.3 Allowing the contingency of natural cause as a predisposing factor for mass famine, this article revisits the Vietnam famine of 1944-45 in light of flaws in human agency (alongside willful or even deliberate neglect) as well as destabilization stemming from war and conflict. While I avoid the issue of impacts of the famine in favor of seeking cause - the human suffering of the famine has not been effaced by time. It was recorded in Hanoi newspapers at the time. It survives in local memory and in fiction by Vietnamese writers.4The great famine was never construed as a war crime by the Allies, yet the question of blame, alongside agency or lack of it, was an issue between the French and the Viet Minh in the immediate aftermath of the Japanese surrender and entered into propaganda recriminations. Indeed, as written into the Democratic Republic of Vietnam (DRV) declaration of independence, both Japan and France were jointly blamed for the disaster. South Vietnam (the Republic of Vietnam) also raised the famine issue in postwar reparation negotiations with Japan. While such charged issues as the Nanjing Massacre, the comfort women, forced labor and unit 731 have long been the subject of intense debate in the historical memory wars, in textbook controversies and museum exhibits, the Vietnamese famine, and Japan’s role in creating it, appear to have disappeared from Japanese war memory and commemoration whether in textbooks or museum representations. It may nevertheless be asked, why is it important now to apportion blame? I would argue that the great Vietnam famine of 1944-45 is at least one of the underwritten tragedies stemming from the Pacific War. Outside of Vietnam, very few articles or studies have sought to contextualize this event, whether from the side of Vietnamese history, or from the perspective of Japanese and/or French and American responsibility. No doubt a court of law would seek to distinguish between deliberate policy, benign neglect, and/or the unanticipated consequences of social action. But, rather than pinning blame as with a court of law or a war crimes trial, what I seek here is closer to a truth commission-style investigation that precisely seeks to uncover a number of thinly veiled truths that could possibly stimulate further research, not only on war and memory issues related to the famine, but also in the field of famine prevention.